Parameters of strength fitness in athletes from various team sports - Maksimenko, I. G.; Maksimenko, G. N.; Spirin, M. P.; Mironova, T. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to identify the parameters of strength fitness of athletes of different skill levels from various team sports and conduct a comparative analysis of the data obtained.